METHODOLOGY OF PROFESSIONAL PEDAGOGICAL EDUCATION: THEORY AND PRACTICE (THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF VOCATIONAL TEACHER EDUCATION) - E. M. Dorozhkin; E. F. Zeer (Образование и наука)
The study is aimed at investigating a justification of the new approach to the problem of vocational education development through the prism of interdependence research methodology and practice. This conceptual setup allows determining the main directions for teacher training modernization of vocational schools.The authors note that the current socio-economic situation in our country has actualized the problem of personnel training. Politicians, economists and scientists’ speeches are all about the shortage of skilled personnel. They see the main reason of this catastrophic situation in the present system of primary andsecondary vocational education. At least they concern over the current practice of pedagogical personnel training of vocational education who are to restore the system of vocational education. Our country, Russia has a great positive experience in solving this problem. Scientific-methodological centre for vocational teacher education is the Russian State Vocational Pedagogical University under the scientific direction of Academicianof the Russian Academy of Education, G. M. Romantsev. The reflection of scientific-theoretical bases of this education led the authors to the analysis and designing (formation) of existent and new professional and pedagogical methodology. Methods. The fundamental position of A. M. Novikov on the generality of theresearch (scientific) and practical activity methodology has become the theoretical platform of the present study. Conceptual field, conceptual statements and professional model are presented as the whole system (or integrating factor). The theoretical framework has determined the logic of the study and its results.Scientific and educational methodology differentiation in terms of the subject of cogni live activity has allowed identifying the main scientific and practical disciplines of vocational teacher education. The creative concept as the subject ground is instrumental analysis of methodology taking into consideration the target orientation, principles and approaches to the organization and its’ methods of scientific and educational activitiesimplementation. The qualification structure formation of the teachers’ vocational training and providing advance principles of education are considered to be the most important conditions for the development of vocational teacher education.Scientific novelty. The research demonstrates creating the project of further vocational teacher education development in the post-industrial society. The pedagogical innovations transforming research findings into educational practice are considered to be the main tool of integration methodology means.Practical significance. The research findings highlight the proposed reforms for further teachers training system development of vocational institutes, which are in need of drastic restructuring. In the final part of the article the authors recommend some specific issues that can be discussed at the methodological workshop.